Induction of neutralizing antibody response against four dengue viruses in mice by intramuscular electroporation of tetravalent DNA vaccines - Eakachai Prompetchara (2018)
DNA vaccine against dengue is an interesting strategy for a prime/boost approach. This study evaluated neutralizing antibody (NAb) induction of a dengue tetravalent DNA (TDNA) vaccine candidate administered by intramuscular- electroporation (IM-EP) and the benefit of homologous TDNA boosting in mice. Consensus humanized pre-membrane (prM) and envelope (E) of each serotypes, based on isolates from year 1962-2003, were separately cloned into a pCMVkan expression vector. ICR mice, five-six per group were immunized for three times (2-week interval) with TDNA at 100 μg (group I; 25 μg/monovalent) or 10 μg (group II; 2.5 mg/monovalent). In group I, mice received an addtional TDNA boosting 13 weeks later. Plaque reduction neutralization tests (PRNT) were performed at 4 weeks post-last immunization. Both 100 mg and 10 mg doses of TDNA induced high NAb levels against all DENV serotypes. The median PRNT50 titers were comparable among four serotypes of DENV after TDNA immunization. Median PRNT50 titers ranged 240-320 in 100 μg and 160-240 in 10 μg groups (p = ns). A time course study of the 100 μg dose of TDNA showed detectable NAb at 2 weeks after the second injection. The NAb peaked at 4 weeks after the third injection then declined over time but remained detectable up to 13 weeks. An additional homologous TDNA boosting significantly enhanced the level of NAb from the nadir for at least ten-fold (p < 0.05). Of interest, we have found that the use of more recent dengue viral strain for both vaccine immunogen design and neutralization assays is critical to avoid a mismatching outcome. In summary, this TDNA vaccine candidate induced good neutralizing antibody responses in mice; and the DNA/DNA prime/boost strategy is promising and warranted further evaluation in non-human primates. © 2014 Prompetchara et al.